Fungal endophyte Phomopsis liquidambari affects nitrogen transformation processes and related microorganisms in the rice rhizosphere - Yang, Bo; Wang, Xiaomi; Ma, Haiyan; Yang, Teng; Jia, Yong; Zhou, Jun; Dai, Chuanchao (Frontiers in Microbiology, 2015)
The endophytic fungus Phomopsis liquidambari performs an important ecosystem service by assisting its host with acquiring soil nitrogen (N), but little is known regarding how this fungus influences soil N nutrient properties and microbial communities. In this study, we investigated the impact of P. liquidambari on N dynamics，the abundance and composition of N cycling genes in rhizosphere soil treated with three levels of N (urea). Ammonia-oxidizing archaea (AOA), ammonia-oxidizing bacteria (AOB) and diazotrophs were assayed using quantitative real-time polymerase chain reaction and denaturing gradient gel electrophoresis at four rice growing stages (S0: before planting, S1: tillering stage, S2: grain filling stage, and S3: ripening stage). A significant increase in the available nitrate and ammonium contents was found in the rhizosphere soil of endophyte-infected rice under low N conditions. Moreover, P. liquidambari significantly increased the potential nitrification rates (PNR), affected the abundance and community structure of AOA, AOB and diazotrophs under low N conditions in the S1 and S2 stages. The root exudates were determined due to their important role in rhizosphere interactions. P. liquidambari colonization altered the exudation of organic compounds by rice roots and P. liquidambari increased the concentration of soluble saccharides, total free amino acids and organic acids